Combined effects of particulate matter (PM) and ultraviolet B (UVB) co-treatment induced oxidative stress and cellular damage on human epithelial keratinocytes HaCaT: Acute and chronic environmental exposure analysis - Piriyapratankun Praepilai; Cheunmatcha Peerawut; Kwanthongdee Jaturon; Pongkorpsakol Pawin; Leerach Nontaphat; Chatsirisupachai Anyamanee (E3S Web of Conferences)
Environmental contaminants have recently attracted attention because of their severe atmospheric concentration and long-term negative health consequences, such as inflammatory and carcinogenic effects. This study investigated the adverse effects of daily environmental exposures including particulate matter (PM) and ultraviolet B (UVB), individually and in combination, on HaCaT keratinocytes, focusing on cell viability and oxidative stress under acute and chronic conditions. Keratinocytes were treated with various doses of PM and UVB reflective of real-world exposure: 12.5, 25, 50, 100, 200 µg/mL for PM and 25, 50, 75, 100, 200 mJ/cm2 for UVB irradiation. Cytotoxicity was investigated using cell viability assay and reactive oxygen species (ROS) generation was observed by using 2′,7′-Dichlorodihydrofluorescein Diacetate staining prior to flow cytometry analysis. Treatment with PM or UVB individually demonstrated dose-dependent and significantly decline in cell viability. In addition, the additive effects were exhibited in PM and UVB co-treatment conditions. Flow cytometry analysis of co-treatments revealed the strong effects on cellular damages, indicative of programmed cell death. The mechanistic studies showed that co-exposure slightly elevated ROS levels upon chronic exposure, suggesting adverse complications in oxidative damage. These findings underscore the harmful effects of PM and UVB on keratinocytes, emphasizing the need to address combined environmental stressors.